Stress-strain condition monitoring of bearing structures in order to ensure safety in the operation of high-rise buildings - Ryabtsev Виталий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
In the paper discusses the issues of fire hazard features of high-rise buildings with the specifics of their engineering and construction in the Republic of Belarus. The problem of introducing systems construction monitoring of the stress-strain state of load-bearing structures of tall buildings on the construction and operation stages are reviewed. The structure and operation principles of vector optical fiber interferometric sensor of displacements and stresses are proposed.